A Description of COVID-19-Directed Therapy in Children Admitted to US Intensive Care Units 2020. Issue 5 (12th January 2022) - Schuster, Jennifer E; Halasa, Natasha B; Nakamura, Mari; Levy, Emily R; Fitzgerald, Julie C; Young, Cameron C; Newhams, Margaret M; Bourgeois, Florence; Staat, Mary A; Hobbs, Charlotte V; Dapul, Heda; Feldstein, Leora R; et al.
Abstract: Background: It is unclear how acute coronavirus disease 2019 (COVID-19)-directed therapies are used in children with life-threatening COVID-19 in US hospitals. We described characteristics of children hospitalized in the intensive care unit or step-down unit (ICU/SDU) who received COVID-19-directed therapies and the specific therapies administered. Methods: Between March 15, 2020 and December 27, 2020, children <18 years of age in the ICU/SDU with acute COVID-19 at 48 pediatric hospitals in the United States were identified. Demographics, laboratory values, and clinical course were compared in children who did and did not receive COVID-19-directed therapies. Trends in COVID-19-directed therapies over time were evaluated. Results: Of 424 children in the ICU/SDU, 235 (55%) received COVID-19-directed therapies. Children who received COVID-19-directed therapies were older than those who did not receive COVID-19-directed therapies (13.3 [5.6-16.2] vs 9.8 [0.65-15.9] years), more had underlying medical conditions (188 [80%] vs 104 [55%]; difference = 25% [95% CI: 16% to 34%]), more received respiratory support (206 [88%] vs 71 [38%]; difference = 50% [95% CI: 34% to 56%]), and more died (8 [3.4%] vs 0). Of the 235 children receiving COVID-19-directed therapies, 172 (73%) received systemic steroids and 150 (64%) received remdesivir, with rising remdesivir use over the study period (14% in March/April to 57% November/December). Conclusion: Despite the lack of pediatric data evaluating treatments for COVID-19 in critically ill children, more than half of children requiring intensive or high acuity care received COVID-19-directed therapies. Abstract : No therapies for acute coronavirus disease 2019 (COVID-19) have been tested in children to establish effectiveness. Despite this, across 48 hospitals, 235/424 children (55%) admitted to the intensive care or step-down unit with COVID-19 received directed therapies. Systemic steroids and remdesivir were most commonly administered, with use rising from March 2020 to December 2020.